El homenaje de una carta y de un sermón - Osorio Torres, Juan Alberto (2011)
This is a contextualized article of Pastoral Theology in relation to its anthropology comprehension, since the commemoration of the three first diocesan lustra with a new ecclesiastical community collective identity and the foundation of a parish in the sandy area of the south of Lima by Maryknoll priests. This fact is compared by the author with “Montesinos's Sermon”, pronounced at the end of the first decade of the XVI century, taking into account that those are episodes or symbolic expressions of a unique and always valid process, the institutionalization of the Church, through their dioceses. The pastoral implications of an ecclesiastic community installment and functioning have always an evangelic and prophetic character